722 NATURAL ACTIVATORS OF AUTOPHAGY PROTECT THE HEART FROM DOX-INDUCED CARDIOMYOPATHY. (15th December 2022) - Schirone, Leonardo; Vecchio, Daniele; Forte, Maurizio; Sciarretta, Sebastiano
Abstract: Introduction: Heart failure is a frequent death cause for oncological patients who received treatment with doxorubicin (DOX). DOX administration inhibits autophagy in cardiomyocytes and causes myocardial damage. Natural activators of autophagy (NAA) such as trehalose, a natural disaccharide, and spermidine, a putrescine-derived polyamine initially isolated from semen, were previously found to be promising candidates to recover the autophagic flux and treat cardiovascular diseases in mice. Hypothesis: The administration of natural activators of autophagy protects the heart from DOX-induced myocardial injury. Methods: C57BL/6J WT mice were fed ad libitum with trehalose or spermidine in drinking water and received 3 weekly injections of DOX, reaching a final cumulative dose of 15 mg/kg. Echocardiographic, histological and biochemical analyses were performed 6 weeks after the first administration of DOX. Also, in vitro experimentation was performed on neonatal rat primary cardiomyocytes. Results: Mice treated with DOX had reduced systolic function (FS: 44±1.05% vs. 34.1±2.33%, n=6-8), but trehalose administration preserved left ventricular fractional shortening (FS: 34.1 [Office1] ±2.33% vs. 45.1±0.75%, n=6-8). Autophagy-deficient Beclin1 +/- mice had reduced FS and were not protected by trehalose administration (35.4±2.48% vs. 45.1±0.75%, n=7-8). Mice treated with DOX developed fibrosis (0.1±0.08% vs. 8.6±3.5%, n=5), but this effect was reduced in trehalose-fed mice that received DOX (8.6±3.5% vs. 2±0.68%, n=4-5). DOX administration increased the levels of damaged-mitochondria disposal (2.6±0.74 vs. 9.4±1.7 mitophagic bodies per TEM field, n=13) and trehalose administration further boosted this effect (9.4±1.7 vs. 24.1±1.45, n=13). The mRFP-eGFP-Lc3-dots assay was used for evaluating the autophagic flux in neonatal primary cardiomyocytes and a reduction of autophagy was observed in cells treated with DOX (51.9±4.57 vs. 29.9±3.52 red dots per cell, n=34-51), while trehalose recovered the autophagic flux (29.9±3.52 vs. 121.5±8.02 red dots per cell, n=33-34). Mitochondrial biogenesis reporter 'MitoTimer' mice that received DOX showed increased levels of biogenesis (0.8±0.38 vs. 3.3±0.9, n=5-6), while mice receiving DOX and trehalose did not (3.3±0.9 vs. 0.3±0.12, n=5-6). Similarly, spermidine preserved systolic function (FS: 29.4±2.03 vs. 39±3.22, n=5-6) and increased myocardial autophagy. Conclusion: NAA-mediated mitophagy induction protects the heart from developing DOX-induced cardiomyopathy by disposing of damaged mitochondria. [Office1]Le virgole diventano punti